Ghana on the Go : African Mobility in the Age of Motor Transportation - Hart, Jennifer A. (Jennifer Anne) (Book collections on Project MUSE., 2016)
As early as the 1910s, African drivers in colonial Ghana understood the possibilities that using imported motor transport could further the social and economic agendas of a diverse array of local agents, including chiefs, farmers, traders, fishermen, and urban workers. Jennifer Hart's powerful narrative of auto-mobility shows how drivers built on old trade routes to increase the speed and scale of motorized travel. Hart reveals that new forms of labor migration, economic enterprise, cultural production, and social practice were defined by autonomy and mobility and thus shaped the practices and values that formed the foundations of Ghanaian society today. Focusing on the everyday lives of individuals who participated in this century of social, cultural, and technological change, Hart comes to a more sensitive understanding of the ways in which these individuals made new technology meaningful to their local communities and associated it with their future aspirations.